The Relationship between NAFLD and Sarcopenia in Elderly Patients - Yu Zhai; Qian Xiao; Jing Miao (Canadian Journal of Gastroenterology and Hepatology)
Aim. Previous studies have shown that individuals with low muscle mass exhibit an increased risk of nonalcoholic fatty liver disease (NAFLD). In this study, we investigated the association between NAFLD and sarcopenia in elderly patients. Methods. We classified the participants into sarcopenia/nonsarcopenia groups based on dual-energy X-ray absorptiometry (DXA), muscle strength (grip strength), or/and physical performance (6 m usual gait speed). We diagnosed NAFLD by ultrasonography combined with the history of alcohol intake. Logistic regression analysis was used to assess the correlation between sarcopenia and NAFLD. Results. NAFLD was significantly less frequent in the sarcopenia group than in the nonsarcopenia group (P<0.01). However, NAFLD was neither an independent risk factor nor a protective factor for sarcopenia. Conclusions. NAFLD is not independently associated with sarcopenia.